Gastric and Rectal Metastases from Malignant Melanoma Presenting with Hypochromic Anemia and Treated with Immunotherapy. (12th October 2017) - Genova, Pietro; Sorce, Maria; Cabibi, Daniela; Genova, Gaspare; Gebbia, Vittorio; Galanti, Daniela; Ancona, Chiara; Valerio, Maria Rosaria
Abstract : The authors present a case of an 80-year-old Caucasian male with multiple gastric and rectal metastases from malignant melanoma presenting with hypochromic anemia as the sole symptom of disease without evidence of cutaneous and ocular tumor localization. The patient had a medical history positive for malignant lentigo melanoma of the occipital region of the scalp and early stage laryngeal squamous cell carcinoma and prostatic carcinoma treated with radiation therapy. The authors make some considerations on intestinal involvement by metastatic melanoma and discuss the choice of not treating with endoscopic procedures the gastric metastatic lesions most likely responsible for the clinical sign present at diagnosis. The patient was referred to clinical oncologists and received immunotherapy with ipilimumab and pembrolizumab.